Implementasi Implementasi Pembelajaran Berdiferensiasi dalam Meningkatkan Keterampilan Kolaborasi Siswa Sekolah Dasar - kurnia, adila (Indonesian Journal of Educational Science (IJES), 2024)
Differentiated learning is an action taken by the teacher in the classroom that adapts the learning process to the needsof each student, so that the needs of each child can be met as a whole. One of the main needs of students that needs tobe improved in achieving optimal learning outcomes and supporting the learning process in the surroundingenvironment is the ability to collaborate. The purpose of this study was to find out whether there was an increase instudents' collaboration skills using a differentiated learning model. The type of research used is collaborativeclassroom action research with four stages, namely: planning, action, observation, and reflection. This research wasconducted at Gendongan 01 Public Elementary School with research subjects namely all 22 grade II students. Dataanalysis techniques used percentage, category, and comparison techniques. In the pre-cycle, students' collaborationskills reached 9.09%. After applying differentiated learning, collaboration skills can increase in the first cycle by40.09% and in the second cycle by 72.71%. The use of differentiated learning models can also improve student learningoutcomes, which were originally in the pre-cycle as much as 45.45%, increased to 72.72% in cycle I and cycle II asmuch as 90.90%. Thus, the differentiated learning model can be applied in learning to improve collaboration skills andstudent learning outcomes.